Ecosystem services of partial organic substitution for chemical fertilizer in a peri-urban zone in China. (1st July 2019) - Tang, Quan; Ti, Chaopu; Xia, Longlong; Xia, Yongqiu; Wei, Zhijun; Yan, Xiaoyuan
Abstract: Chemical nitrogen fertilizer application in the peri-urban zone has benefited food supply, but excess nitrogen input has altered multiple ecosystem services and caused an array of ecosystem dis-services that have degraded air and water quality. Using sewage sludge compost and pig manure to partially substitute chemical fertilizer nitrogen may promote sustainable ecosystem services. However, few studies have been conducted to evaluate the values of associate ecosystem services with a unified standard. To comprehensively understand the effect of partial organic substitution on ecosystem services (supporting vegetable production and sequestering soil organic carbon) and ecosystem dis-services (greenhouse gas emissions and reactive nitrogen release), we attempted to evaluate the ecosystem service from the perspective of economic assessment. A field experiment was conducted in a peri-urban zone in eastern China, including the following six treatments at equal total nitrogen application rates: (1) no fertilizer nitrogen applied; (2) 25% sewage sludge compost substitution; (3) 25% pig manure substitution; (4) 50% sewage sludge compost substitution; (5) 50% pig manure substitution and (6) chemical fertilizer nitrogen only. The results showed that partial organic substitution significantly increased annual vegetable yield by 27.8%–35.3% and annual soil organic carbon sequestration rate by 129.2%–213.8%. Moreover, greenhouse gas emissions (methane and nitrous oxide) were significantly decreased by 28.6%–43.2%; nitrogen leaching and runoff were significantly decreased by 39.0%–49.5% and 26.8%–62.0%, respectively; and ammonia volatilization was increased by 2.4%–27.8%. Overall, partial substitution with organic fertilizer decreased total reactive nitrogen losses by 19.9%–39.8% compared with the 100% chemical fertilizer nitrogen treatment. Although additional labor and higher input costs were required, partial organic substitution could obtain a higher net economic benefit of 25198–90670 ¥ ha −1  yr −1 compared with the sole application of chemical fertilizer nitrogen. The results suggest that partial substitution of chemical fertilizer with organic fertilizer can sustain ecosystem services and reduce ecosystem dis-services in the peri-urban zone and increase economic profits for farmers. Graphical abstract: Image 1 Highlights: Ecosystem services in a peri-urban zone were evaluated with a unified standard. Organic fertilizer substitution increased ecosystem services by increasing vegetable yield and C sequestration in soil. Organic fertilizer substitution decreased ecosystem dis-services by decreasing GHG emissions and reactive N losses.